Taxonomic revision of the genus Flemingia (Leguminosae) from Indo-Chinese floristic region - Do, Truong Van; Gao, Xin-Fen (Phytotaxa, 2020)
In present research, we revised the taxonomy of Flemingia for the whole Indochinese floristic region, which consist of 24 species and one variety. China was the most diversified country with 18 species of Flemingia and one variety, followed by Myanmar (16 species), Thailand (13 species and one variety), Vietnam (12 species and one variety), Laos (12 species and one variety), and Cambodia (5 species). Flemingia weii is newly described from China, F. sootepensis and F. nana are new records for China, F. kerrii and F. mengpengensis are new records for Myanmar, and F. semialata is a new record for Vietnam and China. Based on the identity of morphological characters, we synonymized F. ferruginea var. eglandulosa, F. yunnanensis, F. kradungensis, F. tiliaceae under F. kerrii, F. macrophylla, F. kweichowensis, F. strobilifera, respectively. Furthermore, the lectotype of F. ferruginea var. eglandulosa and F. lineata var. hirtella are designated here. For each species, accepted names, literature, synonyms, type specimens, full description, iconography citation, ecology, phenology, distribution and taxonomic notes with morphologically characters have been studied in detials. In order to facilitate species identification and delimitation, a dichotomous key to the known species of Flemingia within the Indochinese floristic region was provided. Additionally, some doubtful species were also discussed.